Measurement of differential cross sections for inclusive isolated-photon and photon plus jet production in proton-proton collisions at root s=13TeV - Sirunyan, A. M. (2019)
Measurements of inclusive isolated-photon and photon+jet production in proton-proton collisions at =13TeV are presented. The analysis uses data collected by the CMS experiment in 2015, corresponding to an integrated luminosity of 2.26fb-1. The cross section for inclusive isolated photon production is measured as a function of the photon transverse energy in a fiducial region. The cross section for photon+jet production is measured as a function of the photon transverse energy in the same fiducial region with identical photon requirements and with the highest transverse momentum jet. All measurements are in agreement with predictions from next-to-leading-order perturbative QCD.